Pola Pendidikan Anak Dalam Keluarga Perspektif Ibnu Khaldun - Inti Astutik; Norma Ita Solichah (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This article examines Ibn Khaldun's thoughts on children's education patterns in the context of the family as the first and foremost educational institution. Through the literature study method, this study found that Ibn Khaldun had a comprehensive and visionary view of education, which not only emphasized the intellectual aspect, but also included the development of faith and spirituality, morals and social, life skills, and the development of an independent and disciplined attitude. He emphasized the importance of gradual, contextual, and experience-based education, and rejected rigid teaching methods that suppressed children's creativity. His ideas are very relevant in answering the problems of today's children's education, especially related to the dichotomy between religious and general education, as well as the declining role of the family due to the influence of globalization and technological advances. This study recommends the importance of integrating Islamic values into the modern curriculum, strengthening the role of the family in children's education, and developing learning strategies that can foster 21st-century character and skills.